Betel Quid, Smoking and Alcohol Dependency among Patients with Oral Potentially Malignant Disorders and Oral Cancer in Sri Lanka; A Preliminary Case-control Study - R. Sumithrarachchi, Sumali; Pemasiri, W.A.Udari.C.; Pathiranage, A.M.S. Deepanie.; Jayasooriya, Primali R. (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: Oral cancer and Oral Potentially Malignant Disorders (OPMDs) arising due to risk habits like betel quid (BQ) chewing, smoking and alcohol use are preventable despite the high prevalence and poor survival rates. However, dependence to risk habits has become a barrier to prevent OPMDs and oral cancer. Objectives: This study was conducted to determine the dependence to risk habits among patients with such oral lesions, and the quitting among dependent users after diagnosis. Materials and method: A case-control study was conducted among 100 participants, 50 diagnosed with OPMDs and oral cancer from two Oral and Maxillo Facial clinics in Sri Lanka and a similar control group without any oral lesions. All participants practiced one or more risk habits such as BQ chewing, smoking and/or alcohol use. Dependence was assessed using Sinhala language translations of standardized scales such as Betel Quid Dependence Scale for BQ chewers, Fagerstrom Test for Nicotine Dependence for tobacco smokers and CAGE (“Cut down”, “Annoyed”, “Guilty” and “Eye opener”) scale for alcohol users. Results: Dependence on habits was more among the case group (BQ-93%; smoking-14%; alcohol-66%). Quitting rates of BQ and alcohol among those who were diagnosed with oral cancer [BQ (89%), alcohol (89%)] were higher (p<0.05) than those with OPMDs [BQ (50%), alcohol (22%)]. Lack of awareness due to low socio-economic status (97%) was a significant association for BQ dependence (p=0.01). Conclusion: In conclusion, development of OPMDs and oral cancer increases with dependence to BQ chewing, smoking and alcohol use. Increased awareness about OPMDs and its risk of malignancy is needed among public. Prevention of dependence to these risk habits also becomes essential.